The Effects of Including Cinnamaldehyde or Carvacrol in Wethers’ Diets on the Main Parameters of Rumen Metabolism - Alexandra - Gabriela Oancea; Catalin Dragomir; Ana Cismileanu (Scientific Papers Animal Science and Biotechnologies, 2023)
Essential oils are plants’ secondary metabolites that have the potential to be valorized as feed additives. Literature background indicates that cinnamaldehyde (main component of the cinnamon oil) and carvacrol (present in oregano leaves) possess properties that might influence the rumen metabolism. In order to assess this potential, a 3x3 Latin square experimental design was organized using three wethers fed diets supplemented with cinnamaldehyde or carvacrol. The pH, ammonia concentrations and VFA concentrations (total and individual) of the rumen fluid were determined at the each of each experimental period. Supplementation with cinnamaldehyde and, in a lesser extent, with carvacrol significantly improved some of the parameters related to the rumen pH level. Slight decreases, not statistically significant, was observed in case of ammonia and total VFA concentrations, for both cinnamaldehyde- and carvacrol-supplemented diets. However, the cinnamaldehyde-supplemented diet significantly influenced the VFA profile, leading to a decrease of the butyric acid (p=0.044) and a decrease tendency for valeric acid (p=0.067). These changes confirmed the potential of the two essential oils to influence the rumen metabolism, especially in the case of cinnamaldehyde.